Peran servicescape terhadap trust dan dampaknya pada minat beli yang dimoderasi oleh personal selling pada live streaming produk tas di facebook - Qiven Daud; Virgo Simamora (Jurnal Riset Pendidikan Ekonomi, 2022)
This study aims to examine the effect of servicescape and trust on interest in buying bags moderated by personal selling. This research was conducted in the Greater Jakarta area. The sampling technique used purposive sampling method. This research data is primary data collected by distributing questionnaires to consumers using live streaming on Facebook. Hypothesis testing was carried out using the PLS data analysis method. based on statistical tests, the results of the study show that servicescape has a positive and significant effect on trust and significantly on buying interest. While personal selling moderation has no significant effect on buying interest